2023
DOI: 10.1108/tlo-01-2023-0019
|View full text |Cite
|
Sign up to set email alerts
|

The state-of-the-art of modern workplace learning: an applied assessment method of a pre-train deep learning on modern learning tools

Abstract: Purpose The study discusses the importance of workplace learning in the current era of work and how organisations are shifting their focus toward employee learning and development. It highlights the need for employees to continuously up-skill themselves to keep up with the demand for skills. The purpose of this study is to introduce a modern approach to evaluating workplace learning to promote and enhance better performance within the workplace. Design/methodology/approach It introduces a deep modern learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
7
0
4
Order By: Relevance
“…Previous research has shown that modern professionals are more likely to remain with companies that offer various learning opportunities (D’Amato and Herzfeldt, 2008), turning workplace learning into a useful instrument for talent retention (Muzam et al , 2023). This has practical implications for human resources and organizational development.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has shown that modern professionals are more likely to remain with companies that offer various learning opportunities (D’Amato and Herzfeldt, 2008), turning workplace learning into a useful instrument for talent retention (Muzam et al , 2023). This has practical implications for human resources and organizational development.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…This has practical implications for human resources and organizational development. As employees only learn when it is relevant and appealing, organizations need to constantly adapt their learning capabilities (Muzam et al , 2023). The flexibility of implementing WOL could offer a viable alternative to static “off the job” learning.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gamification refers to the use of game-like elements in non-game settings (Deterding et al, 2011), typically in the workplace, to enhance employee productivity, organizational productivity and employee well-being (Oprescu et al, 2014). While gamification has been extensively studied in formal learning contexts, little is known about its impact on informal learning, where employees often learn more efficiently and effectively (Billett, 2004;Froehlich et al, 2014;Muzam et al, 2023).…”
Section: Introductionmentioning
confidence: 99%